DIGITAL WORLDS, DIGITAL RELIGION AND RESILIENCE: CHILDREN AND ADOLESCENTS IN NETWORKED SOCIETIES - Dusan Luzny (PEOPLE: International Journal of Social Sciences, 2026)
Rapidly developing digital technologies, particularly those related to digital communication, represent a major turning point in the functioning of contemporary societies worldwide. Although increasing digital accessibility does not eliminate persistent forms of digital exclusion, the widespread availability of smartphones and access to mobile data and online networks has undergone a profound transformation in recent years. This shift increasingly affects children and adolescents, for whom the digital world—and especially social media platforms—constitutes a primary arena of socialisation, identity formation and peer interaction. Parallel to these developments, religion and spirituality are undergoing significant transformations, giving rise to what scholars have conceptualised as digital religion or digital spirituality (Campbell 2013). Processes such as the digitalisation of leisure time, social relationships and modes of communication are not merely technical changes, but deeply social and cultural ones. They reshape how religious symbols, narratives and practices are accessed, interpreted and integrated into everyday life. In this sense, digitalisation may be understood as one of the most far-reaching transformations of late modern societies, intensifying ongoing processes of individualisation and detraditionalisation. Against this backdrop, the conference paper discusses the risks and opportunities that digital religion presents for children and adolescents, with particular attention to questions of resilience. Digital environments can expose young people to fragmented and sometimes contradictory symbolic repertoires, potentially amplifying experiences of uncertainty or vulnerability. At the same time, online spaces may offer new forms of community, meaning-making and emotional support, including hybrid religious and spiritual expressions that are loosely connected to institutional traditions but nonetheless draw on their symbolic resources. The paper adopts a primarily theoretical and methodological focus. It reflects on how existing sociological and religious-studies approaches to religion, socialisation and resilience can be adapted to the study of digital contexts, and it discusses the methodological challenges of researching children’s engagement with digital religion. Particular attention is paid to the implications of these processes for understanding resilience in highly secularised societies.